Literature Review: The Integration of Financial Patriotism and Digitalization within National Economic Resilience - Fadillah, Achmad; Indrawati (Li Falah: Journal of Islamic Economics and Business, 2026)
National economic resilience is strongly influenced by the role of Micro, Small, and Medium Enterprises (MSMEs) as the main pillar of the domestic economy, particularly amid global economic pressures and the acceleration of digitalization. In this context, the concept of financial patriotism has become increasingly relevant as a foundation for economic behavior that is oriented not only toward profit generation but also toward contributing to national development. This study employs a literature review method by analyzing scientific articles published between 2021 and 2025 and obtained through Google Scholar. The findings indicate that the implementation of financial patriotism values, such as the use of domestic financial systems and preferences for local products, contributes to maintaining economic circulation and strengthening the national economic structure. On the other hand, digitalization has a significant impact on improving the efficiency, productivity, and market access of MSMEs. However, disparities in technology adoption remain a challenge that must be addressed through the strengthening of digital infrastructure, the enhancement of digital literacy, and support from various stakeholders. The integration of financial patriotism and digitalization serves as a key factor in developing adaptive, innovative, and competitive MSMEs, thereby supporting sustainable national economic resilience.